CIVIL SOCIETY BEFORE GLOBALIZATION CHALLENGES - Черноног, Р. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2010)
The article deals with the analysis of tendencies and perspectives of the modern civil society transformation in connection with the globalization processes.